DEVELOPMENT OF MATHEMATICS MODULE IN TRIGONOMETRY MATERIAL BASED ON DISCOVERY LEARNING FOR GRADE 10TH - Nesti Puspandari; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Limited learning resources is a problem that affects the achievement of learning goals. Teaching materials that can help students learn independently with or without a teacher's guidance is a module. This research is the development research to compose a mathematics module in trigonometry material based on discovery learning for grade 10th of Senior High School (SMA). Knowing the module that is developed is suitable or not if used in a mathematics lesson. This research usesÂ  Research and Development to identify potential and problems, collect the information, design a product, design validation, design revision, experiment, and product revision. This research and development of the module are material expert, media expert, and students in SMA Muhammadiyah 3 Yogyakarta and SMA Muhammadiyah 7 Yogyakarta. The Mathematics Module is developed using a Likert scale that changes the qualitative value into a quantitative value based on discovery learning. Data collection techniques in the form of interviews and questionnaires. The research results indicate that the mathematics module in statistics material based on discovery learning for grade 10th of SMA/MA has a good quality seen from the validity criteria. Based on material experts and media experts' assessment, an average score is 89,67 and 104, including very well criteria. The student's response to the module indicates that the module's good quality obtained an average score is 76,58. Based on the research results, the mathematics module in trigonometry material based on discovery learning for grade 10th of SMA/MA is suitable for the mathematics lesson.